Aluminum alloy containing anticorrosive coating and preparation method thereof
Through the multi-layer protection mechanism of zirconate conversion film, ZnO and Zn powder and epoxy resin, the corrosion problem of aluminum alloy in harsh environments is solved, efficient and long-lasting anti-corrosion performance is achieved, and the long-term stable operation of aluminum alloy is ensured. and performance maintenance.
Patent Information
- Application Number
- CN202411462022.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-10-01
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-14
AI Technical Summary
Aluminum alloys are prone to corrosion in complex or harsh environments, resulting in degradation of equipment stability and performance. Existing anti-corrosion measures are difficult to effectively delay or prevent corrosion reactions.
The synergistic effect of zirconate conversion film, ZnO and Zn powder in composite coatings and epoxy resin coatings is used to form a multi-layer protection mechanism to improve the corrosion resistance of aluminum alloys. Zirconate films provide physical barriers and chemical stability, ZnO and Zn powders are filled in the coating to increase density and provide sacrificial anode protection when the coating is damaged, and epoxy resins provide physical barriers as the outermost line of defense.
It achieves good condition maintenance of aluminum alloy in harsh environments, significantly improves its corrosion resistance, ensures effective corrosion resistance and long-term stability of the coating, prevents corrosive media from invading, and extends the service life of the equipment.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of alloy surface corrosion protection, and specifically relates to an aluminum alloy containing an anti-corrosion coating and a preparation method thereof. Background Art
[0002] As one of the indispensable materials in modern industry, aluminum alloy plays an important role in many fields such as industry, construction, and transportation due to its unique physical and chemical properties. However, aluminum alloy is prone to corrosion during use, especially under complex or harsh environmental conditions. This problem poses a significant challenge to the long-term stable operation and performance maintenance of equipment. The corrosion of aluminum alloy mainly comes from its interaction with the surrounding environment. For example, oxygen, water vapor, acid and alkali substances in the air and other corrosive media (such as salt spray, industrial waste gas, etc.) may cause erosion on the surface of aluminum alloy; in addition, the microstructure and chemical composition inside the aluminum alloy are also important factors affecting its corrosion resistance. Once the protective film on the surface of the aluminum alloy (such as the natural oxide film) is destroyed, the exposed base metal will quickly react with the corrosive medium in the environment to form corrosion products. The corrosion process will not only cause the thickness of the aluminum alloy material to be thinned and the size to change, but also cause a significant decrease in its mechanical properties (such as strength and toughness). In extreme cases, corrosion can also cause stress concentration, leading to the sudden fracture of aluminum alloy structural parts, which seriously threatens the safety and service life of the equipment.
[0003] In view of the severity and universality of aluminum alloy corrosion, its anti-corrosion work has received much attention and importance from various industries. The purpose of anti-corrosion is to delay or prevent the reaction between aluminum alloy and corrosive media in the environment through a series of measures, thereby protecting its surface and internal structure from damage, so as to ensure that aluminum alloy equipment can operate stably for a long time and maintain good performance under complex or harsh environmental conditions.
[0004] Therefore, developing an efficient and long-lasting aluminum alloy containing an anti-corrosion coating has become one of the problems that technical personnel in this field urgently need to solve. Summary of the invention
[0005] In view of the deficiencies in the prior art, the present invention discloses an aluminum alloy containing an anti-corrosion coating and a preparation method thereof, wherein the corrosion resistance of the aluminum alloy is improved through the synergistic effect of the zirconate conversion film, ZnO and Zn powder in the composite coating, and the epoxy resin coating.
[0006] To achieve the above object, the present invention provides the following technical solutions: The invention discloses a method for preparing an aluminum alloy containing an anti-corrosion coating, comprising the following steps: (1) treating the aluminum alloy substrate by ultrasonic cleaning, grinding, and pickling to obtain a pretreated aluminum alloy substrate; (2) soaking the pretreated aluminum alloy substrate obtained in step (1) in a zirconate solution for 2 to 5 minutes, and after the solution is evenly covered on the surface of the aluminum alloy, washing and drying to obtain an aluminum alloy substrate coated with a zirconate conversion film; (3) Add ZnO and Zn powder to epoxy resin respectively, stir and disperse them, then add defoamer, leveling agent, dispersant and curing agent in sequence, and wait until they are evenly dispersed to obtain an anti-corrosion composite coating; (4) Using a spray gun, spray the anti-corrosion composite coating obtained in step (3) onto the aluminum alloy substrate obtained in step (2), heat and solidify the sprayed aluminum alloy substrate, and then cool it naturally, thereby obtaining an aluminum alloy containing an anti-corrosion coating.
[0007] Preferably, in step (1), the ultrasonic cleaning time is 20-30 minutes; the polishing process is as follows: the aluminum alloy substrate that has been ultrasonically cleaned is polished with 240-mesh, 320-mesh, and 400-mesh water-abrasive sandpaper in sequence; the pickling process is as follows: the cleaned and polished aluminum alloy substrate is placed in a 5% dilute sulfuric acid solution, and soaked at 20-30°C for 3-5 minutes to remove the oxide scale remaining on the surface of the aluminum alloy substrate.
[0008] Preferably, in step (2), the zirconate solution is prepared as follows: ZrOCl2·8H2O and NH4F are added to water, stirred and mixed to obtain a mixed solution, and then ammonia water is added dropwise to the mixed solution and stirred and mixed until the pH value of the solution is 3.5-4.5, that is, a zirconate solution is obtained.
[0009] Preferably, the concentrations of ZrOCl2·8H2O and NH4F in the solution are both 10 g / L.
[0010] Preferably, in step (2), the thickness of the zirconate conversion film is 2-3 μm; the drying temperature is 115-120° C., and the drying time is 15-20 min.
[0011] Preferably, in step (3), the components of the anti-corrosion composite coating are calculated by weight as follows: 50-70 parts of epoxy resin, 10-20 parts of ZnO, 5-10 parts of Zn powder, 0.1-0.5 parts of defoaming agent, 0.1-0.5 parts of leveling agent, 0.5-2 parts of dispersant, and 10-20 parts of curing agent.
[0012] Preferably, the defoaming agent is polydimethylsiloxane, the leveling agent is an acrylic leveling agent, the dispersant is one of polyoxyethylene ether, polyacrylate, and carboxylate; and the curing agent is phthalic anhydride or maleic anhydride.
[0013] Preferably, in step (4), the process parameters of the spray gun during spraying are: spraying pressure of 3-6 bar, spraying vertical distance of 160-200 mm, and spraying speed of 0.6-1 m / s.
[0014] Preferably, in step (4), the curing process is divided into: a first stage of low-temperature pre-curing and a second stage of high-temperature main curing; the temperature of the first stage of low-temperature pre-curing is 55-65°C and the insulation time is 1-1.5 hours, and the temperature of the second stage of high-temperature main curing is 100-110°C and the insulation time is 1.5-2 hours.
[0015] The invention also discloses an aluminum alloy containing an anti-corrosion coating, and the aluminum alloy containing the anti-corrosion coating can be prepared by adopting the above preparation method.
[0016] Compared with the prior art, the present invention has the following beneficial effects: The present invention discloses an aluminum alloy with an anti-corrosion coating and a preparation method thereof. The corrosion resistance of the aluminum alloy is improved through the synergistic effect of the zirconate conversion coating, ZnO and Zn powder in the composite coating, and the epoxy resin coating. This multi-layer protection mechanism ensures the effective corrosion resistance of the coating and can keep the aluminum alloy in a good state even in harsh environments. The specific mechanism is as follows: (1) The physical properties of the zirconate conversion film itself enable it to act as a barrier to prevent corrosive substances from penetrating into the metal matrix. At the same time, the zirconate conversion film has high chemical stability and can form a dense protective layer on the surface of the aluminum alloy. This protective layer can effectively prevent corrosive media (such as water and oxygen) from contacting the aluminum alloy matrix, thereby preventing corrosion.
[0017] (2) ZnO has good chemical stability and can be filled in epoxy resin coatings to increase the density of the coating, reduce the porosity, and improve the protective ability of the coating. In addition, zinc powder has a lower standard electrode potential and is more easily oxidized than aluminum. When the coating is damaged, zinc will be corroded first and act as a sacrificial anode. The corrosion products of zinc (such as Zn (OH) 2) can form a passivation layer on the surface of the aluminum alloy, further preventing the invasion of corrosive media, thereby protecting the aluminum alloy substrate from corrosion.
[0018] The present invention improves the corrosion resistance of aluminum alloy through a multi-layer protection mechanism, from the inside out: the zirconate conversion film serves as the first line of defense, providing physical isolation and chemical stability; the ZnO and Zn powder in the composite coating serve as the second line of defense, ZnO increases the density and stability of the coating, and the Zn powder provides additional sacrificial anode protection when the coating is damaged; and the epoxy resin coating serves as the outermost line of defense; together they constitute an effective anti-corrosion system. DETAILED DESCRIPTION
[0019] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0020] The invention discloses an aluminum alloy containing an anti-corrosion coating and a preparation method thereof, wherein the preparation method comprises the following steps: (1) After ultrasonic cleaning for 20-30 min, the aluminum alloy substrate was polished with 240-mesh, 320-mesh, and 400-mesh water-abrasive sandpaper in sequence. The cleaned and polished aluminum alloy substrate was then placed in a 5% dilute sulfuric acid solution at 20-30°C for 3-5 min to remove the oxide scale remaining on the surface of the aluminum alloy substrate, thereby obtaining a pretreated aluminum alloy substrate.
[0021] (2) Soaking the pretreated aluminum alloy substrate obtained in step (1) in a zirconate solution for 2 to 5 minutes, and after the solution is evenly covered on the surface of the aluminum alloy, washing it, and drying it at 115 to 120° C. for 15 to 20 minutes to obtain an aluminum alloy substrate with a surface coating of a zirconate conversion film having a thickness of 2 to 3 μm.
[0022] The preparation method of the zirconate solution in this step is as follows: ZrOCl2·8H2O and NH4F are added to water and stirred and mixed, so that the concentrations of ZrOCl2·8H2O and NH4F in the solution are both 10 g / L to obtain a mixed solution, and then ammonia water is added dropwise to the mixed solution and stirred and mixed until the pH value of the solution is 3.5-4.5, that is, a zirconate solution is obtained.
[0023] (3) By weight: add 10-20 parts of ZnO and 5-10 parts of Zn powder to 50-70 parts of epoxy resin, stir and disperse, then add 0.1-0.5 parts of defoamer (polydimethylsiloxane), 0.1-0.5 parts of leveling agent (acrylic leveling agent), 0.5-2 parts of dispersant (one of polyoxyethylene ether, polyacrylate, carboxylate) and 10-20 parts of curing agent (phthalic anhydride or maleic anhydride) in sequence, and wait for uniform dispersion to obtain an anti-corrosion composite coating.
[0024] (4) spraying the anti-corrosion composite coating obtained in step (3) on the aluminum alloy substrate obtained in step (2) by using a spray gun under the following process parameters: spraying pressure of 3-6 bar, spraying vertical distance of 160-200 mm, and spraying speed of 0.6-1 m / s; then subjecting the sprayed aluminum alloy substrate to a first stage of low-temperature pre-curing at a temperature of 55-65° C. and keeping the temperature for 1-1.5 h; then raising the temperature to 100-110° C. and keeping the temperature for 1.5-2 h, subjecting the substrate to a second stage of high-temperature main curing, and then cooling the substrate naturally, thereby obtaining an aluminum alloy containing an anti-corrosion coating.
[0025] The technical solution of the present invention is further described below in conjunction with specific embodiments: Example 1
[0026] The method for preparing an aluminum alloy containing an anti-corrosion coating in this embodiment specifically comprises the following steps: (1) After ultrasonic cleaning for 20 minutes, the aluminum alloy substrate was polished with 240 mesh, 320 mesh, and 400 mesh water-abrasive sandpaper in sequence. The cleaned and polished aluminum alloy substrate was then placed in a 5% dilute sulfuric acid solution at 25°C for 3 minutes to remove the oxide scale remaining on the surface of the aluminum alloy substrate, thereby obtaining a pretreated aluminum alloy substrate.
[0027] (2) The pretreated aluminum alloy substrate obtained in step (1) was immersed in a zirconate solution for 3 min, wherein the concentrations of ZrOCl2·8H2O and NH4F in the solution were both 10 g / L and the pH value of the solution was 3.5. After the solution was evenly covered on the surface of the aluminum alloy, it was washed and dried at 115°C for 18 min to obtain an aluminum alloy substrate with a surface coating of a zirconate conversion film with a thickness of 2.0 μm.
[0028] (3) By weight: add 15 parts of ZnO and 8 parts of Zn powder to 60 parts of epoxy resin, stir and disperse them, then add 0.3 parts of polydimethylsiloxane, 0.2 parts of acrylic leveling agent, 0.8 parts of polyoxyethylene ether and 15 parts of phthalic anhydride in sequence, and wait until they are evenly dispersed to obtain an anti-corrosion composite coating.
[0029] (4) Under the conditions of a spraying pressure of 4 bar, a spraying vertical distance of 160 mm, and a spraying speed of 0.8 m / s, the anti-corrosion composite coating prepared in step (3) is sprayed on the aluminum alloy substrate prepared in step (2) using a spray gun; the sprayed aluminum alloy substrate is then placed in an oven and kept at 60° C. for 1 hour, the temperature is then raised to 100° C. and kept at this temperature for 1.5 hours, and then naturally cooled, thereby obtaining an aluminum alloy containing an anti-corrosion coating. Example 2
[0030] The method for preparing an aluminum alloy containing an anti-corrosion coating in this embodiment specifically comprises the following steps: (1) After ultrasonic cleaning for 25 minutes, the aluminum alloy substrate was polished with 240 mesh, 320 mesh, and 400 mesh water-abrasive sandpaper in sequence. The cleaned and polished aluminum alloy substrate was then placed in a 5% dilute sulfuric acid solution at 30°C for 5 minutes to remove the oxide scale remaining on the surface of the aluminum alloy substrate, thereby obtaining a pretreated aluminum alloy substrate.
[0031] (2) The pretreated aluminum alloy substrate obtained in step (1) was immersed in a zirconate solution for 5 min, wherein the concentrations of ZrOCl2·8H2O and NH4F in the solution were both 10 g / L and the pH value of the solution was 4.0. After the solution was evenly covered on the surface of the aluminum alloy, it was washed and dried at 120°C for 15 min to obtain an aluminum alloy substrate with a surface coating of a zirconate conversion film with a thickness of 2.5 μm.
[0032] (3) By weight: add 20 parts of ZnO and 10 parts of Zn powder to 70 parts of epoxy resin respectively, stir and disperse, then add 0.3 parts of polydimethylsiloxane, 0.4 parts of acrylic leveling agent, 1.0 parts of polyacrylate and 10 parts of phthalic anhydride in sequence, and wait until they are evenly dispersed to obtain an anti-corrosion composite coating.
[0033] (4) Under the conditions of a spraying pressure of 6 bar, a spraying vertical distance of 200 mm, and a spraying speed of 1.0 m / s, the anti-corrosion composite coating prepared in step (3) is sprayed on the aluminum alloy substrate prepared in step (2) using a spray gun; the sprayed aluminum alloy substrate is then placed in an oven and kept at 65° C. for 1.5 h, the temperature is then raised to 110° C. and kept at this temperature for 1.5 h, and then naturally cooled, thereby obtaining an aluminum alloy containing an anti-corrosion coating. Example 3
[0034] The method for preparing an aluminum alloy containing an anti-corrosion coating in this embodiment specifically comprises the following steps: (1) After ultrasonic cleaning for 30 minutes, the aluminum alloy substrate was polished with 240 mesh, 320 mesh, and 400 mesh water-abrasive sandpaper in sequence. The cleaned and polished aluminum alloy substrate was then placed in a 5% dilute sulfuric acid solution at 20°C for 5 minutes to remove the oxide scale remaining on the surface of the aluminum alloy substrate, thereby obtaining a pretreated aluminum alloy substrate.
[0035] (2) The pretreated aluminum alloy substrate obtained in step (1) was immersed in a zirconate solution for 2 min, wherein the concentrations of ZrOCl2·8H2O and NH4F in the solution were both 10 g / L and the pH value of the solution was 4.0. After the solution was evenly covered on the surface of the aluminum alloy, it was washed and dried at 120°C for 15 min to obtain an aluminum alloy substrate with a surface coating of zirconate conversion film with a thickness of 2.2 μm.
[0036] (3) By weight: add 10 parts of ZnO and 10 parts of Zn powder to 50 parts of epoxy resin respectively, stir and disperse, then add 0.1 parts of polydimethylsiloxane, 0.1 parts of acrylic leveling agent, 0.5 parts of polyacrylate and 10 parts of maleic anhydride in sequence, and wait until they are evenly dispersed to obtain an anti-corrosion composite coating.
[0037] (4) Under the conditions of a spraying pressure of 3 bar, a spraying vertical distance of 160 mm, and a spraying speed of 0.6 m / s, the anti-corrosion composite coating prepared in step (3) is sprayed on the aluminum alloy substrate prepared in step (2) using a spray gun; the sprayed aluminum alloy substrate is then placed in an oven and kept at 55° C. for 1.5 h, then the temperature is raised to 110° C. and kept at this temperature for 2 h, and then naturally cooled, thereby obtaining an aluminum alloy containing an anti-corrosion coating. Example 4
[0038] The method for preparing an aluminum alloy containing an anti-corrosion coating in this embodiment specifically comprises the following steps: (1) After ultrasonic cleaning for 30 minutes, the aluminum alloy substrate was polished with 240 mesh, 320 mesh, and 400 mesh water-abrasive sandpaper in sequence. The cleaned and polished aluminum alloy substrate was then placed in a 5% dilute sulfuric acid solution at 30°C for 5 minutes to remove the oxide scale remaining on the surface of the aluminum alloy substrate, thereby obtaining a pretreated aluminum alloy substrate.
[0039] (2) The pretreated aluminum alloy substrate obtained in step (1) was immersed in a zirconate solution for 5 min, wherein the concentrations of ZrOCl2·8H2O and NH4F in the solution were both 10 g / L and the pH value of the solution was 4.5. After the solution was evenly covered on the surface of the aluminum alloy, it was washed and dried at 115°C for 15 min to obtain an aluminum alloy substrate with a surface coating of a zirconate conversion film with a thickness of 3 μm.
[0040] (3) By weight: add 20 parts of ZnO and 5 parts of Zn powder to 60 parts of epoxy resin, stir and disperse them, then add 0.3 parts of polydimethylsiloxane, 0.3 parts of acrylic leveling agent, 2 parts of polyacrylate and 15 parts of maleic anhydride in sequence, and disperse them evenly to obtain an anti-corrosion composite coating.
[0041] (4) Under the conditions of a spraying pressure of 4 bar, a spraying vertical distance of 180 mm, and a spraying speed of 0.8 m / s, the anti-corrosion composite coating prepared in step (3) is sprayed on the aluminum alloy substrate prepared in step (2) using a spray gun; the sprayed aluminum alloy substrate is then placed in an oven and kept at 65° C. for 1.5 h, then the temperature is raised to 100° C. and kept at this temperature for 2 h, and then naturally cooled, thereby obtaining an aluminum alloy containing an anti-corrosion coating. Comparative Example 1
[0042] The difference between this comparative example and the above-mentioned embodiment 1 is that this comparative example directly adopts epoxy resin for spraying.
[0043] (1) After ultrasonic cleaning for 20 minutes, the aluminum alloy substrate was polished with 240 mesh, 320 mesh, and 400 mesh water-abrasive sandpaper in sequence. The cleaned and polished aluminum alloy substrate was then placed in a 5% dilute sulfuric acid solution at 25°C for 3 minutes to remove the oxide scale remaining on the surface of the aluminum alloy substrate, thereby obtaining a pretreated aluminum alloy substrate.
[0044] (2) The pretreated aluminum alloy substrate obtained in step (1) was immersed in a zirconate solution for 3 min, wherein the concentrations of ZrOCl2·8H2O and NH4F in the solution were both 10 g / L and the pH value of the solution was 3.5. After the solution was evenly covered on the surface of the aluminum alloy, it was washed and dried at 115°C for 18 min to obtain an aluminum alloy substrate with a surface coating of a zirconate conversion film with a thickness of 2.0 μm.
[0045] (3) Under the conditions of a spraying pressure of 4 bar, a spraying vertical distance of 160 mm, and a spraying speed of 0.8 m / s, the epoxy resin coating is sprayed on the aluminum alloy substrate obtained in step (2) using a spray gun; the sprayed aluminum alloy substrate is then placed in an oven and kept at 60° C. for 1 hour, and then the temperature is raised to 100° C. and kept at this temperature for 1.5 hours, and then naturally cooled, thereby obtaining an aluminum alloy containing an anti-corrosion coating. Comparative Example 2
[0046] The difference between this comparative example and the above-mentioned Example 2 is that: when curing the sprayed aluminum alloy substrate in this comparative example, the substrate is directly kept at 110° C. for 1.5 hours.
[0047] (1) After ultrasonic cleaning for 25 minutes, the aluminum alloy substrate was polished with 240 mesh, 320 mesh, and 400 mesh water-abrasive sandpaper in sequence. The cleaned and polished aluminum alloy substrate was then placed in a 5% dilute sulfuric acid solution at 30°C for 5 minutes to remove the oxide scale remaining on the surface of the aluminum alloy substrate, thereby obtaining a pretreated aluminum alloy substrate.
[0048] (2) The pretreated aluminum alloy substrate obtained in step (1) was immersed in a zirconate solution for 5 min, wherein the concentrations of ZrOCl2·8H2O and NH4F in the solution were both 10 g / L and the pH value of the solution was 4.0. After the solution was evenly covered on the surface of the aluminum alloy, it was washed and dried at 120°C for 15 min to obtain an aluminum alloy substrate with a surface coating of a zirconate conversion film with a thickness of 2.5 μm.
[0049] (3) By weight: add 20 parts of ZnO and 10 parts of Zn powder to 70 parts of epoxy resin respectively, stir and disperse, then add 0.3 parts of polydimethylsiloxane, 0.4 parts of acrylic leveling agent, 1.0 parts of polyacrylate and 10 parts of phthalic anhydride in sequence, and wait until they are evenly dispersed to obtain an anti-corrosion composite coating.
[0050] (4) Under the conditions of a spraying pressure of 6 bar, a spraying vertical distance of 200 mm, and a spraying speed of 1.0 m / s, the anti-corrosion composite coating prepared in step (3) is sprayed on the aluminum alloy substrate prepared in step (2) using a spray gun; the sprayed aluminum alloy substrate is then placed in an oven at 110° C. for 1.5 h, and then naturally cooled, thereby obtaining an aluminum alloy containing an anti-corrosion coating.
[0051] The aluminum alloys with anti-corrosion coatings prepared in the above Examples 1-4 and the aluminum alloys with anti-corrosion coatings prepared in Comparative Examples 1 and 2 were subjected to ASTM B117 salt spray test, and calibration was performed according to the requirements of ASTM B117. The samples were fixed on the brackets in the test box to ensure that the distance between the sample and the nozzle met the standard requirements, and the sample was placed at an angle of 20° to ensure that the salt spray was evenly deposited on its surface. In the test, the salt solution was a 5% NaCl solution with a pH value of 7.0. The temperature of the test box was 35±2°C, and the salt spray deposition rate was 1.5 ml / hour / 80 square centimeters for 200 days. The salt spray test box was closed, the sample was taken out, and the surface of the sample was rinsed with low-pressure tap water to remove the salt spray deposits. The sample was then blown dry, and the corrosion condition (rust, discoloration, blistering) on the surface of the sample was observed. The results are shown in Table 1.
[0052] Table 1
[0053] As can be seen from Table 1, after 200 days of salt spray corrosion testing in a 5% NaCl aqueous solution and a neutral salt spray condition at a temperature of 35±2°C: (a) the coatings in Examples 1-4 exhibit excellent corrosion resistance. Specifically, there is no sign of rust, discoloration or blistering on the coating surface, which indicates that the corrosion-resistant coating prepared by the formula and preparation method disclosed in the present invention can still maintain a high degree of stability and integrity after long-term exposure to a corrosive environment, which fully demonstrates that the aluminum alloy containing the corrosion-resistant coating prepared by the present invention has efficient and durable corrosion resistance. (b) Compared with Examples 1-4, the coating surface of Comparative Column 1 showed rust. This contrast clearly revealed the importance of the anti-corrosion system formed by the synergistic action of ZnO, Zn and epoxy resin; ZnO can effectively isolate the direct contact between the corrosive medium and the substrate, Zn further enhances the anti-corrosion effect through the sacrificial anode protection mechanism, and epoxy resin, as an excellent film-forming substance, provides a strong physical barrier; the three work together to build an efficient and lasting anti-corrosion barrier, which is significantly better than Comparative Column 1 which lacks this complete system. (c) Compared with Examples 1-4, the blistering phenomenon on the coating surface of Comparative Column 2 reflects the criticality of the staged curing process from the side; blistering is often caused by the failure of bubbles generated during the coating curing process to be discharged in time, or the presence of uneven stress inside the coating. The staged curing process of the present invention promotes the full cross-linking of resin molecules and the effective release of gas by accurately controlling the curing temperature and time of each stage, thereby ensuring the uniform curing of the coating and high-quality surface morphology, not only reducing the generation of bubbles and stress, but also significantly improving the hardness and durability of the coating, providing a solid guarantee for the long-term anti-corrosion protection of aluminum alloys. Therefore, the present invention achieves efficient and long-lasting anti-corrosion performance of the anti-corrosion coating on the surface of aluminum alloys through a multi-layer protection mechanism and an optimized curing process.
[0054] The above is a detailed introduction to an aluminum alloy containing an anti-corrosion coating and a preparation method thereof disclosed in the present invention. Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. It should be pointed out that for ordinary technicians in this technical field, without departing from the principles of the present invention, several improvements and modifications can be made to the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.
Claims
1. A method for preparing an aluminum alloy containing an anti-corrosion coating, characterized in that: The following steps are involved: (1) treating the aluminum alloy substrate by ultrasonic cleaning, grinding, and pickling to obtain a pretreated aluminum alloy substrate; (2) soaking the pretreated aluminum alloy substrate obtained in step (1) in a zirconate solution for 2 to 5 minutes, and after the solution is evenly covered on the surface of the aluminum alloy, washing and drying to obtain an aluminum alloy substrate coated with a zirconate conversion film; (3) Add ZnO and Zn powder to epoxy resin respectively, stir and disperse them, then add defoamer, leveling agent, dispersant and curing agent in sequence, and wait until they are evenly dispersed to obtain an anti-corrosion composite coating; (4) Using a spray gun, spray the anti-corrosion composite coating obtained in step (3) onto the aluminum alloy substrate obtained in step (2), heat and solidify the sprayed aluminum alloy substrate, and then cool it naturally, thereby obtaining an aluminum alloy containing an anti-corrosion coating.
2. The method for preparing an aluminum alloy containing an anti-corrosion coating according to claim 1, characterized in that: In step (1), the ultrasonic cleaning time is 20-30 minutes; the polishing process is as follows: the aluminum alloy substrate that has been ultrasonically cleaned is polished with 240-mesh, 320-mesh, and 400-mesh water-abrasive sandpaper in sequence; the pickling process is as follows: the cleaned and polished aluminum alloy substrate is placed in a 5% dilute sulfuric acid solution, and soaked at 20-30° C. for 3-5 minutes to remove the oxide scale remaining on the surface of the aluminum alloy substrate.
3. The method for preparing an aluminum alloy containing an anti-corrosion coating according to claim 1, characterized in that: In step (2), the preparation method of the zirconate solution is as follows: ZrOCl2·8H2O and NH4F are added to water, and a mixed solution is obtained by stirring, and then ammonia water is added dropwise to the mixed solution and stirred and mixed until the pH value of the solution is 3.5-4.5, that is, a zirconate solution is obtained.
4. The method for preparing an aluminum alloy containing an anti-corrosion coating according to claim 3, characterized in that: The concentrations of ZrOCl2·8H2O and NH4F in the solution are both 10 g / L.
5. The method for preparing an aluminum alloy containing an anti-corrosion coating according to claim 4, characterized in that: In step (2), the thickness of the zirconate conversion film is 2-3 μm; the drying temperature is 115-120° C., and the drying time is 15-20 min.
6. The method for preparing an aluminum alloy containing an anti-corrosion coating according to claim 1, characterized in that: In step (3), the components of the anti-corrosion composite coating are calculated by weight as follows: 50-70 parts of epoxy resin, 10-20 parts of ZnO, 5-10 parts of Zn powder, 0.1-0.5 parts of defoaming agent, 0.1-0.5 parts of leveling agent, 0.5-2 parts of dispersant, and 10-20 parts of curing agent.
7. The method for preparing an aluminum alloy containing an anti-corrosion coating according to claim 6, characterized in that: The defoamer is polydimethylsiloxane, the leveling agent is acrylic leveling agent, the dispersant is one of polyoxyethylene ether, polyacrylate and carboxylate; and the curing agent is phthalic anhydride or maleic anhydride.
8. The method for preparing an aluminum alloy with an anti-corrosion coating according to claim 1, characterized in that: In step (4), the process parameters of the spray gun during spraying are: spraying pressure of 3-6 bar, spraying vertical distance of 160-200 mm, and spraying speed of 0.6-1 m / s.
9. The method for preparing an aluminum alloy containing an anti-corrosion coating according to claim 8, characterized in that: In step (4), the curing process is divided into: a first stage of low-temperature pre-curing and a second stage of high-temperature main curing; the temperature of the first stage of low-temperature pre-curing is 55-65°C and the insulation time is 1-1.5 hours, and the temperature of the second stage of high-temperature main curing is 100-110°C and the insulation time is 1.5-2 hours.
10. Aluminum alloy containing anti-corrosion coating obtained by the preparation method according to any one of claims 1 to 9.